2006
DOI: 10.1373/clinchem.2005.065631
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography–Tandem Mass Spectrometry for Detection of Low Concentrations of 21 Benzodiazepines, Metabolites, and Analogs in Urine: Method with Forensic Applications

Abstract: Background: Commonly used methods for detecting benzodiazepines (BZPs) and BZP-like substances, such as zolpidem and zopiclone, may not detect low concentrations of these drugs. We developed a liquid chromatographic-tandem mass spectrometric method for identifying these drugs and their relevant metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 31 publications
0
38
0
1
Order By: Relevance
“…ESI, as a very soft ionization technique, is the most suitable for labile metabolites, and is therefore preferred in metabolite analysis (Kostiainen et al, 2003). The analysis of benzodiazepines and their metabolites can be performed using ESI-LC-MS (Jourdil et al, 2003) and ESI-LC-tandem mass spectrometry (MS/MS) (Liu et al, 2001;Chèze et al, 2004;Kintz et al, 2005;Laloup et al, 2005;Villain et al, 2005;Hegstad et al, 2006;Miller 358 et al, 2006;Quintela et al, 2006;Feng et al, 2007;Laloup et al, 2007;Li et al, 2007;Moore et al, 2007) as well as APCI-LC-MS (Kratzsch et al, 2004;Bugey et al, 2006) and APCI-LC-MS/MS (Smink et al, 2004(Smink et al, , 2006Ngwa et al, 2007). A conventional reversed-phase C 18 column is popularly used in the abovementioned LC-MS/MS methods.…”
Section: Introductionmentioning
confidence: 99%
“…ESI, as a very soft ionization technique, is the most suitable for labile metabolites, and is therefore preferred in metabolite analysis (Kostiainen et al, 2003). The analysis of benzodiazepines and their metabolites can be performed using ESI-LC-MS (Jourdil et al, 2003) and ESI-LC-tandem mass spectrometry (MS/MS) (Liu et al, 2001;Chèze et al, 2004;Kintz et al, 2005;Laloup et al, 2005;Villain et al, 2005;Hegstad et al, 2006;Miller 358 et al, 2006;Quintela et al, 2006;Feng et al, 2007;Laloup et al, 2007;Li et al, 2007;Moore et al, 2007) as well as APCI-LC-MS (Kratzsch et al, 2004;Bugey et al, 2006) and APCI-LC-MS/MS (Smink et al, 2004(Smink et al, , 2006Ngwa et al, 2007). A conventional reversed-phase C 18 column is popularly used in the abovementioned LC-MS/MS methods.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that ZOP metabolites are excreted mainly unconjugated [142]. Urine samples have also been processed without hydrolysis because of analyte instability during incubation [137]. No hydrolyzing step was used in the method in Paper III.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Some assays (HPLC, LC-MS, LC-MS/MS) have also been developed to separate and determine ZOP [127,[137][138][139] and/or its metabolites (NDZOP and ZOPNO) in urine [140][141][142]. However, because of analytical detection or validation problems when ZOP was analysed in urine, the ZOP analyte was excluded from two of these methods [139,141].…”
Section: Occurrence Of Zopiclone In Forensic Casesmentioning
confidence: 99%
See 2 more Smart Citations